2013
DOI: 10.1074/jbc.c113.457028
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Cerebral Malaria Develops Independently of Endothelial Expression of Intercellular Adhesion Molecule-1 (ICAM-1)

Abstract: Background: Endothelium-expressed intercellular adhesion molecule-1 (ICAM-1) is considered critical for the development of cerebral malaria (CM). Results: ICAM-1 expression on leukocytes alone was sufficient for the development of experimental CM. Conclusion: Endothelial expression of ICAM-1 is not required for development of CM. Significance: Vascular occlusion in CM requires ICAM-1 expression on leukocytes but not endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…More strikingly, the density of ICAM-1 positive leukocytes in postcapillary venules was significantly higher (t-test: T (8) = 4.30, P <0.01) during ECM compared to hyperparasitemia ( Figure 5G ). Thus, ECM is associated with the arrest of large numbers of ICAM-1+ leukocytes, consistent with a recent report on the contribution of leukocyte ICAM-1 to ECM development [66] .…”
Section: Resultssupporting
confidence: 92%
“…More strikingly, the density of ICAM-1 positive leukocytes in postcapillary venules was significantly higher (t-test: T (8) = 4.30, P <0.01) during ECM compared to hyperparasitemia ( Figure 5G ). Thus, ECM is associated with the arrest of large numbers of ICAM-1+ leukocytes, consistent with a recent report on the contribution of leukocyte ICAM-1 to ECM development [66] .…”
Section: Resultssupporting
confidence: 92%
“…Activated effector T cells have been accounted to play a decisive role in the disruption of the BBB and disease progression [ 41 ]. Parasite-specific cell-mediated responses increase systemic and local inflammation, leading to an activation of endothelial cells; genetically deficient mice or depletion strategies had impressively demonstrated the importance of adhesion molecules such the intercellular adhesion molecule 1 (ICAM-1), P-selectin on activated endothelial cells and leukocytes [ 42 , 43 ] in the induction of ECM. In addition, local effector processes such as intravascular accumulation of leukocytes and CD8 + T cells [ 44 ] and the production of granzyme B [ 26 ] and perforin [ 45 , 46 ] during ECM are well described.…”
Section: Discussionmentioning
confidence: 99%
“…In studies simultaneously comparing the course of ECM in different lines of ICAM-1 mutant mice, it has now been shown that the ECM phenotype varies directly with the combination of isoforms expressed (53). Not surprisingly, Icam1 tm1Alb mice were highly resistant to ECM with over 90% of mice surviving ten days post-infection, a time at which all wild type mice had succumbed to disease (Table 1).…”
Section: Does Differential Icam-1 Isoform Expression Alter Disease Phmentioning
confidence: 99%